Improving Chicken Growth Performance with Nano Silver Added to Drinking Water - Al-Jebory, Hashim Hadi; Al-Saeedi, Mohammed Khalil Ibrahim; Al-Khafaji, Fadhil Rasool; Ali, Nihad Abdul-Lateef; Lehmood, B.A.M.; Taheri, Hossein; Qotbi, Ali Ahmed Alaw; Ghazi, Shahab; Sakr, Shimaa A (International Journal of Scientific Research in Biological Sciences, 2023)
Silver nanoparticles (Silver NPs) are among the most potent nanoparticles used in nanoscience. Through a five-week feeding trial, this study examined the effects of various concentrations of (Silver NPs) added to water on broiler chicken growth performance. From 21-3-2019 to 24-4-2019, 225-day-old (Ross 308) broiler chicks were allocated into five random groups, each being replicated three times with 15 birds in each replication. Silver nanoparticles were supplemented to drinking water at 0.0, 20, 30, 40, and 50 ppm/L for groups G1 (control group), G2, G3, G4, and G5, respectively. Our findings showed that the group that received drinking water with 20 ppm/L had a significant advantage over the other groups in terms of body weight at the 4th and 5th weeks and total weight gain throughout the experiment. The overall food conversion ratio of groups that received drinking water containing up to 30 ppm/L significantly improved in groups supplemented with greater concentrations in terms of kg weight growth per kilogram feed intake. The G2 group is the only group that achieved zero mortality compared to the other groups. It was also found that the levels of Nanosilver increased the number of red and white blood cells, hematocrit, and hemoglobin at 14 and 35 days of the age of the broilers. It also increased glucose levels, triglycerides, malondialdehyde (MDA), and the glutathione enzyme at 35 days of the age of the broilers the groups G4 and G5 were the highest.